TERDAPAT PERBEDAAN PENGARUH CIRCUIT BODY WEIGHT TRAINING (CBWT) SUBMAKSIMAL TERHADAP PENURUNAN PERSENTASE LEMAK TUBUH, LEMAK SUBKUTAN DAN MENINGKATKAN OTOT SKELETAL - Pambudi, A. Agam Haris; Liben, Paulus; Rejeki, Purwo Sri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Physical activity with moderate intensity can be implemented with various types of exercise, including multiple movements done in turns which take a bodyweight as a training load known as the circuit body weight training (CBWT). The purpose of this research to prove influence CBWT moderate intensity to the percentage of the body fat, subcutaneous fat and muscles skeletal a person trained and untrained. This is research experimental with the methods pretest-posttest design. 20 people women aged 18 to 23 years was obtained using proportionate stratified random sampling. Consisting of K1 10 people trained and K2 10 people untrained. Done the measurement of the percentage of the body fat, subcutaneous fat and muscles skeletal use weight body composition monitor model HBF-375 Karada scan. The subject is given the treatment CBWT moderate intensity (64-76% heart rate maximum) for 30 menit, after which the measurement was done again 5 minutes after treatment. The data were analyzed using the SPSS statistical tests with paired t-test and the continued independent t-test. Body fat pre K1 mean ∆ (0,53%±0,28), and K2 mean ∆ (0,92%±0,69), the value of p = 0,119 (p